DETERMINAN KINERJA USAHA KECIL MENENGAH PADA PUSAT PERBELANJAAN DI JAKARTA UTARA - Christian, Michael (Jurnal Pengabdian dan Kewirausahaan, 2018)
ABSTRACTIn 2016 the contribution of Gross Domestic Product (GDP) of the Creative Economy sector to the total national economy was almost eight percent. This explains that the Creative Economy continues to provide significant improvements. One sub-sector contained in the Creative Economy is the contribution of fashion which contributes to eighteen percent or is in the top 3 subsectors of the largest contributor to the Creative Economy sector. This study aims to analyze the determinants of the performance factors of fashion businesses in one of the fashion shopping centers in Jakarta. The number of respondents in this study were 144 people. This research model is a Structural Equation Modeling using SMART PLS 3.0. This study explains that the performance of fashion businesses in one of the fashion shopping centers in Jakarta is influenced by market orientation factors, entrepreneurial orientation, business marketing capabilities. In addition, the business performance is also influenced by market orientation factors and factors of entrepreneurial orientation with entrepreneurial skills as mediation. This research also explains that the ability to market by entrepreneurs is influenced by factors of market orientation and entrepreneurial orientation. Dealing with market opportunities and competitor strategies and creating superior strategies such as creating a more attractive boutique layout can be a competitive advantage.Keywords: business performance, market orientation, entrepreneurship, fashion